A note on the Occurrence of Fresh Water Ostracods in the Siwalik Group of Surai Khola Section, Western Nepal - Khosla, S. C.; Upreti, B. N.; Corvinus, G. (Journal of Nepal Geological Society, 1995)
The occurrence of fresh water ostracodes-Candona lactea Baird, Cypria ophthalmica (Jurine), Cyprinotus sp., Jlyocypris gibba (Ramdohr), Limnocythere sp., and Potamocypris sp- is recorded from the Siwalik Group of Surai Khola Section, southeast of Dang in West Nepal.